How Much Leverage is too Much, or Does Corporate Risk Determine the Severity of a Recession? - Ivaschenko, Iryna (IMF Working Papers; Working Paper, 2003)
Economic theory suggests that vulnerable financial conditions of the corporate sector can trigger or worsen an economy-wide recession. This paper proposes a measure of corporate vulnerability, the Corporate Vulnerability Index (CVI) and analyses whether it can explain the probability and severity of recessions. The CVI is constructed as the default probability for the entire corporate sector, using the model of corporate debt by Anderson, Sundaresan, and Tychon (1996). The CVI is shown to be a significant predictor of the probability of a recession 4 to 6 quarters ahead, even controlling for other leading indicators. An increase in the CVI is also associated with an increase in the probability of a more severe and lengthy recession 3 to 6 quarters ahead.